The use of surface electromyography for diagnosis of muscle dysfunction with pain symptoms - Huber, Juliusz; Kulczyk, Aleksandra; Lisiński, Przemysław; Lipiec, Joanna (Akademia Wychowania Fizycznego w Poznaniu)
Surface electromyography (sEMG) is generally considered by neurologists as an unacceptable diagnostic tool for examination of changes in the activity of muscle motor units in patients with non-specific back pain. The aim of this review is to demonstrate the usefulness of neurophysiological findings for the application of sEMG in differentiation of root-conflict and non-root-conflict sources of muscle pathologies with pain as the main symptom. In the first experiment carried out on 30 patients with clinically recognized myofascial pain, an attempt was undertaken to find out whether surface electromyographic (sEMG) readings during relaxation and maximal contraction revealed differences in the activity of muscles with or without trigger points (TrPs) detected by palpation. In the second experiment carried out on 40 office workers similar methodologies of clinical and neurophysiological examination were used, however, with the aim to verify a hypothesis about the dysfunction of cervical and shoulder girdle muscle motor units as the cause of cervicogenic headache (CEH). The results of both experiments led to the following conclusions: 1. Surface EMG performed at rest and during maximal contraction is a precise diagnostic tool that can be used for detection of changes in the activity of motor units in patients with myofascial pain syndrome and cervocogenic headache; 2. Surface EMG readings at rest, with an amplitude exceeding 25ěV, may be helpful for evaluation of increased muscle tension, which leads to a decrease of the activity of muscle motor units during maximal contraction.Surface electromyography (sEMG) is generally considered by neurologists as an unacceptable diagnostic tool for examination of changes in the activity of muscle motor units in patients with non-specific back pain. The aim of this review is to demonstrate the usefulness of neurophysiological findings for the application of sEMG in differentiation of root-conflict and non-root-conflict sources of muscle pathologies with pain as the main symptom. In the first experiment carried out on 30 patients with clinically recognized myofascial pain, an attempt was undertaken to find out whether surface electromyographic (sEMG) readings during relaxation and maximal contraction revealed differences in the activity of muscles with or without trigger points (TrPs) detected by palpation. In the second experiment carried out on 40 office workers similar methodologies of clinical and neurophysiological examination were used, however, with the aim to verify a hypothesis about the dysfunction of cervical and shoulder girdle muscle motor units as the cause of cervicogenic headache (CEH). The results of both experiments led to the following conclusions: 1. Surface EMG performed at rest and during maximal contraction is a precise diagnostic tool that can be used for detection of changes in the activity of motor units in patients with myofascial pain syndrome and cervocogenic headache; 2. Surface EMG readings at rest, with an amplitude exceeding 25ěV, may be helpful for evaluation of increased muscle tension, which leads to a decrease of the activity of muscle motor units during maximal contraction.
Keywords: surface electromyography; muscle resting state; maximal contraction; muscle pain